Time-dependent theoretical description of molecular autoionization produced by femtosecond xuv laser pulses (2006)
ABSTRACT: We present a nonperturbative time-dependent theoretical method to study H2 ionization with femtosecond laser pulses when the photon energy is large enough to populate the Q1 (25–28 eV) and Q2 (30–37 eV) doubly excited autoionizing states. We have investigated the role of these states in dissociative ionization of H2 and analyzed, in the time domain, the onset of the resonant peaks appearing in the proton kinetic energy distribution. Their dependence on photon frequency and pulse duration is also analyzed. The results are compared with available experimental data and with previous theoretical results obtained within a stationary perturbative approach. The method allows us as well to obtain dissociation yields corresponding to the decay of doubly excited states into two H atoms. The calculated H(n=2) yields are in good agreement with the experimental ones.